Double Taxation, Tax Credits and the Information Exchange Puzzle - Wolfgang Eggert (University of Konstanz, Center of Finance and Econometrics (CoFE), 2003)
This paper analyzes the choice of taxes and international information exchange by governments in a capital tax competition model. We explain situations where countries can choose tax rates on tax savings income and exchange information about the domestic savings of foreigners, implying that the decentralized equilibrium is efficient. However, we also identify situations with adverse welfare properties in which information exchange is compatible with zero taxes on capital income. The model helps to identify the linkage between voluntary information exchange and the choice of tax rates. It is shown that the recent development in information exchange treaties may not be useful to overcome the inefficiencies caused by decentralized tax setting.
Keywords: H77; H87; F42; 330; withholding tax; tax credit; international tax competition; information exchange; Doppelbesteuerung; Steuerbegünstigung; Steuerwettbewerb; Kapitalertragsteuer; Informationsverhalten; Theorie; Informationsaustausch